Liberty and Equality: Paradigms for the Protection of Religious Property Use - Carmella, Angela C. (A journal of church and state, 1995)
Angela C. Carmella; Liberty and Equality: Paradigms for the Protection of Religious Property Use, Journal of Church and State, Volume 37, Issue 3, 1 July 1995,